2021
DOI: 10.1002/jbio.202000384
|View full text |Cite
|
Sign up to set email alerts
|

Continuous assessment of metabolic activity of mitochondria using resonance Raman microspectroscopy

Abstract: Dysfunctional mitochondrial activity can lead to a variety of different diseases. As such, there exists a need to quantify changes in mitochondria function as it relates to these specific diseased states. Here, we present the use of resonance Raman (RR) spectroscopy as a tool to determine changes in isolated mitochondrial activity. RR spectroscopy, using 532 nm as the excitation source, specifically provides information on the reduction and oxidation (RedOx) state of cytochrome c, which is determined by the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…7 Surface enhanced Raman spectroscopy uses plasmonic substrate to create local hot spots of electric field enhancement which ultimately increases the efficiency of Raman scattering processes. 8 Resonance Raman spectroscopy utilizing electronic excitation has been also widely used to increase the strength of the signal and can be readily accomplished with cytochrome c 9 and beta carotene in the visible part of the spectrum, and with a large number of organic molecules in the deep UV regime. 10 The above-mentioned improvements improve the signal strengths; however, there is a continuous quest for even higher SNR.…”
Section: Introductionmentioning
confidence: 99%
“…7 Surface enhanced Raman spectroscopy uses plasmonic substrate to create local hot spots of electric field enhancement which ultimately increases the efficiency of Raman scattering processes. 8 Resonance Raman spectroscopy utilizing electronic excitation has been also widely used to increase the strength of the signal and can be readily accomplished with cytochrome c 9 and beta carotene in the visible part of the spectrum, and with a large number of organic molecules in the deep UV regime. 10 The above-mentioned improvements improve the signal strengths; however, there is a continuous quest for even higher SNR.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although many of the features of PBM occur at the "downstream" physiological level, with blood flow and potential amplification via extracellular signaling pathways, we have investigated the detection of immediate effects of photon interaction using in vitro systems. [15][16][17][18][19] Characterizing the fundamental light effects on cells and mitochondria, using rigorous biophysical and enzyme activity methods, can provide valuable information on the initial mechanisms for PBM. It is hoped that knowledge of initial mechanisms of PBM can inform dosimetry requirements for successful induction of PBM therapy in animals and humans that can be translated to enhancing performance.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation wavelength of RRS is usually located in the ultraviolet-visible absorption region, making the laser wavelength equal or close to the absorption peak of the material, which will greatly increase the intensity of Raman signal, and thus lower the limit of detection and reduce the measurement time, making it suitable for the detection of some biological samples. Several studies have reported that RRS could be used to detect mitochondrial function in both isolated cells and tissues [15,16].…”
Section: Introductionmentioning
confidence: 99%